Nomenclatural revision and lectotypification of five species of Mexican oaks: Quercus (Fagaceae) - Valencia-A., Susana; Coombes, Allen J. (Phytotaxa, 2020)
The nomenclature of Quercus splendens, Q. peduncularis, Q. sororia, Q. lancifolia, Q. leiophylla, Q. toxicodendrifolia, Q. gentryi and Q. confertifolia is reviewed by a study of the type specimens, original descriptions and herbarium material. Quercus splendens is regarded as a synonym of Q. peduncularis; Q. sororia and Q. toxicodendrifolia are recognized as accepted names and Q. confertifolia is regarded as the accepted name for Q. gentryi. Fourteen names are lectotypified and one epitype is designated.